2018
DOI: 10.3389/fmolb.2018.00077
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Calcium-Sensing Receptor Corrects the Impaired Mitochondrial Energy Status Observed in Renal Polycystin-1 Knockdown Cells Modeling Autosomal Dominant Polycystic Kidney Disease

Abstract: Autosomal Dominant Polycistic kidney Disease (ADPKD) is a renal channelopathy due to loss-of-function mutations in the PKD1 or PKD2 genes, encoding polycystin-1 (PC1) or polycystin-2 (PC2), respectively. PC1 is a large protein found predominantly on the plasma membrane where interacts with different proteins, including PC2. PC2 is a smaller integral membrane protein also expressed in intracellular organelles, acting as a non-selective cation channel permeable to calcium. Both PC1 and PC2 are also localized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Moreover, we investigated the impact of 2-APB (an antagonist of the IP3 receptor, intracellular Ca 2+ release from ER to the mitochondria) on acetyl-CoA and NAA levels ( Figure 4 A and Figure 6 E). One of the commonly observed side effects of 2-APB is the significant depletion of ATP level, also noted in our study ( Figure 6 C) [ 15 ]. Our further studies revealed that such a shortage is associated with a drop in acetyl-CoA availability ( Figure 6 E).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, we investigated the impact of 2-APB (an antagonist of the IP3 receptor, intracellular Ca 2+ release from ER to the mitochondria) on acetyl-CoA and NAA levels ( Figure 4 A and Figure 6 E). One of the commonly observed side effects of 2-APB is the significant depletion of ATP level, also noted in our study ( Figure 6 C) [ 15 ]. Our further studies revealed that such a shortage is associated with a drop in acetyl-CoA availability ( Figure 6 E).…”
Section: Discussionsupporting
confidence: 81%
“…To establish if acetyl-CoA shortages have the same impact on both NAA and acetylcholine productions, SN56 cells were exposed to mecamylamine (Mec, an antagonist of the nicotinic acetylcholine receptor), nifedipine (NF, an antagonist of the L-type voltage calcium channel) or 2-aminoethoxydiphenyl borate (2-APB, an antagonist of the IP3 receptor). Mec was used to reduce acetylcholine release [ 14 ], nifedipine to reduce free radical production [ 12 ] and 2-APB to evoke ATP shortages [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The disruption in calcium and cAMP signaling cascades activates pathways causing cell proliferation, increased fluid secretion, and interstitial inflammation 116, 117 . Our recent in vitro study demonstrated that in human conditionally immortalized proximal tubular epithelial cells silenced for PKD1 (ciPTEC-PC1KD) or generated from a patient with ADPKD1 (ciPTEC-PC1Pt), selective activation of the calcium-sensing receptor increases cytosolic calcium, reduces intracellular cAMP and mTOR activity 118 , and rescues defective ATP mitochondrial production 119 , reversing the principal ADPKD dysregulations.…”
Section: Vasopressin–aqp2 Pathway In Water Balance Disordersmentioning
confidence: 99%